Annealing temperature assisted microstructural and optoelectrical properties of CdSe thin film grown by RF magnetron sputtering - Rosly H.N.; Rahman K.S.; Harif M.N.; Doroody C.; Isah M.; Misran H.; Amin N. (Academic Press, 2023)
Annealing; Borosilicate glass; Carrier concentration; Energy gap; II-VI semiconductors; Magnetron sputtering; Optical properties; Selenium compounds; Substrates; Thin film solar cells; Thin films; Vacuum furnaces; X ray diffraction; Annealing temperatures; Borosilicate glass substrates; Hall effect measurement; Optoelectrical properties; Preferred orientations; Radio frequency magnetron sputtering; rf-Magnetron sputtering; Solar-cell applications; Cadmium compounds